Inter-organizational workflows: state of the art and trends - Silva, Telmo Eduardo (2011)
Today's workflows are commonly defined beyond organization boudaries and workflow management systems evolution tends to accommodate this recent trend. This type of workflows, implies data exchange between organizations and systems. Various specifications have been proposed to interchange workflow data such as Business Process Execution Language for Web Services (BPEL4WS) and Exchangeable Routing Language (XRL). In this context, this paper presents the state of the art of inter-organizational workflows and the main trends in tecnologies that support them.